Studying the Chemical composition and Physiochemical properties of the Local Kurdish Yogurt(Mast) - Mahmood, Karzan Taufiq; Khalaf, Donia Salman; Mohamad, Dyari Hamakarim (Sulaimani Journal for Pure and Applied Sciences, 2018)
Local Kurdish yogurt (LKY) which is known as Mast has some physical, chemical properties that are effect on the sensory properties, so these properties in the following results are obtained: that showed were significant differences (P ≤ 0.05) of pH among the samples of Kurdish yoghurt(Mast). The lowest pH value of yogurt was in Chaqzh (3.71), while the pH of the Jeshana yogurt was (4.51), which is the highest compared to the rest of the samples. Total acidity in Kulajo yogurt was (1.22%) and was the highest percentage. On the other hand, the lowest percentage in laboratory yogurt (0.58%).In the study of chemical properties it was observed that the significant differences (P ≤ 0.05) were found among the samples. The percentage of moisture and ash in yogurt of Zrgwez samples were highest percentages (85.83% and 0.994%), respectively, whereas the Shekhlangar yogurt had the lowest values of each fat and ash percentages (2.63 and 0.991), respectively. The highest fat content was noticed in Sarkapkan yogurt (4.93%). The percentage of protein tested showed that the yogurt produced in the laboratory had the highest percentage (4.66%), while the lowest percentage was shown in Sarkapkan yogurt (2.54%). Finally, the highest and lowest percentages of total solids were noticed in both yogurt samples of Kanymaran and Zrgwez (17.09 and 14.17%), respectively. Whey separation (syneresis) is one of the physical properties which were tested in this study. The results showed that the significant difference (P ≤ 0.05) was found among the samples, the highest percentage of whey syneresis was observed in Sarkapkan (40.07%) and the lowest percentage of syneresis observed in Kanimaran (30.02%). The yogurt hardness as another physical property of LY, the data showed that significant difference (P ≤ 0.05) were found among the samples, the results showed the highest percentage of hardness was given in Kanymaran yogurt (361.5 g), and the lowest percentage was observed in Chaqzh yogurt (210 g).
Keywords: dairy technology; yogurt; local products; Chemical and Physical properties